A case of esophageal atresia complicated by a right-sided aortic arch with right ductus arteriosus and inferior vena cava interruption with hemiazygos continuation - Terutaka Tanimoto; Takuo Noda; Hiroshi Nouso; Yukinori Miyata (Elsevier, 2022)
During the repair of esophageal atresia with tracheoesophageal fistula (EA/TEF), cardiovascular malformations occasionally create a technical challenge. We report a novel case of a 4-day-old girl with EA/TEF and multiple cardiovascular malformations, including right-sided aortic arch (RAA), right ductus arteriosus (RDA), single ventricle with single atrium, common atrioventricular valve, pulmonary atresia, bilateral superior vena cava, and interruption of the inferior vena cava (IVC) with hemiazygos continuation. In this case, a right-sided approach would require the mobilization of the RAA and RDA, which were supplying the pulmonary blood flow due to pulmonary atresia. Alternatively, the left-sided approach would require the mobilization of the hemiazygos vein, which was essential for venous return from the lower body due to IVC interruption. We performed the less intrusive left-sided approach, and the postoperative course was uneventful. Right-sided EA/TEF repair should be avoided because RDA spasm or injury caused by RAA mobilization would be fatal. In cases of interrupted IVC with azygos or hemiazygos vein continuation, care must be taken not to ligate these vessels or block the venous return. Preoperative evaluation is important to prevent complications in such complicated cases. If sufficient information is not available, the left-sided approach may be preferred.